p53 Related Protein Kinase is Required for Arp2/3-Dependent Actin Dynamics of Hemocytes in Drosophila melanogaster - Molina, Emiliano; Cataldo, Vicente F.; Eggers, Cristián; Muñoz-Madrid, Valentina; Glavic, Álvaro (Frontiers in Cell and Developmental Biology, 2022)
Cells extend membrane protrusions like lamellipodia and filopodia from the leading edge to sense, to move and to form new contacts. The Arp2/3 complex sustains lamellipodia formation, and in conjunction with the actomyosin contractile system, provides mechanical strength to the cell. Drosophila p53-related protein kinase (Prpk), a Tsc5p ortholog, has been described as essential for cell growth and proliferation. In addition, Prpk interacts with proteins associated to actin filament dynamics such as α-spectrin and the Arp2/3 complex subunit Arpc4. Here, we investigated the role of Prpk in cell shape changes, specifically regarding actin filament dynamics and membrane protrusion formation. We found that reductions in Prpk alter cell shape and the structure of lamellipodia, mimicking the phenotypes evoked by Arp2/3 complex deficiencies. Prpk co-localize and co-immunoprecipitates with the Arp2/3 complex subunit Arpc1 and with the small GTPase Rab35. Importantly, expression of Rab35, known by its ability to recruit upstream regulators of the Arp2/3 complex, could rescue the Prpk knockdown phenotypes. Finally, we evaluated the requirement of Prpk in different developmental contexts, where it was shown to be essential for correct Arp2/3 complex distribution and actin dynamics required for hemocytes migration, recruitment, and phagocytosis during immune response.